The role of technology-based CRM and knowledge management In increasing the opportunities of commercial banks to achieving a profits - Abdeghafar Elsayed, Aziza Tawfik (International Journal of Psychosocial Rehabilitation, 2020)
: Objective of this research: To study the technology-based effect of CRM and improve opportunities for profit for commercial banks. And to determine the effect on the increase of commercial banks ' profitability of marketing knowledge management. This work would enhance empirical research into technology- based CRM and marketing information management in commercial banking, in particular in Iraq..Research results can help commercial banking develop effective marketing strategies, particularly commercial banking marketers. This investigation is a quantitative study. The work is conceived as a formal study (by the degree to which the research problem was crystallized) and as a causal study (by research purposes) using purposeful sampling and multiple regression analysis The data was analyzed using the SPSS research. Results show that the impact of technology-based CRM and information management are important in improving business banks ' opportunities to make a profit.